Lichen Planus After Denosumab - Höppner, Jakob; Susok, Laura; Gambichler, Thilo; Grasemann, Corinna (Osteologie, 2023)
Lichenoid reactions have been described as a side effect of several drugs. Here we describe the development of lichen planus (LP) of the mammilla following off-label use of denosumab in an adolescent patient with mono-ostotic fibrous dysplasia. Lichen planus is considered an autoimmune disorder. Since receptor activator of nuclear factor κΒ ligand (RANKL), the target of denosumab action, has regulatory function in the immune system, it is feasible, that LP may be caused as part of an immunological dysregulation.
Keywords: Denosumab; Lichen planus; Therapy